EFFECTS OF PREFERENCE ON THE EMERGENCE OF UNTRAINED VERBAL OPERANTS. Issue 2 (19th April 2013) - Gilliam, Alysia; Weil, Timothy M.; Miltenberger, Raymond G.
Abstract The current study replicated and extended the findings of Wallace, Iwata, and Hanley (2006), who demonstrated conditions that facilitated the transfer from tact to mand relations. Students in the current study were taught to tact both high‐preference (HP) and low‐preference (LP) items and subsequently were assessed on their ability to mand for those items. The results showed the emergence of mands for HP items but not LP items following tact training.